Do Migrant Remittances Promote Corruption in Pakistan? - Alamdar, Anam; Ahmed, Munazza; Jadoon, Atif Khan (iRASD Journal of Economics, 2022)
Remittances play a very important role in a political economy perspective that how do remittances impact corruption in the recipient economy? This paper explored the hypothesis that whether the remittances worked as a cure by decreasing corruption being a political resource (accountability perspective), or remittances worked as a curse by allowing the government to divert spending from public goods provision (substitution perspective). The autoregressive distributed lag (ARDL) method is used to check whether a long-run equilibrium exists among selected indicators from 1984 to 2018. The Error Correction Model was used to get the short-run regression results. Empirical analyses have shown the support for remittances being a curse, not a cure for Pakistan in the long run whereas, short-run results revealed reversed resource curse hypothesis.